Capital Markets and the Instability of Open Economies - Philippe Aghion; Philippe Bacchetta; Abhijit Banerjee (Swiss National Bank, Study Center Gerzensee, 2000)
This paper introduces a framework for analyzing the role of financial factors as a source of instability in small open economies. Our basic model is a dynamic open economy model with one tradeable and one non-tradeable good with the non-tradeable being an input to the production of the tradeable. We also assume that firms face credit constraints, with the constaint being tighter at a lower level of financial development. The two basic implications of this model are the following: first, economies at an intermediate level of financial development are more unstable than either very developed or very underdeveloped economies. This is true both in the sense that temporary shocks have large and persistenst effects and also in the sense that these economies can exhibit stable limit cycles. Thus, countries that are going through a phase of financial development may become more unstable in the short run. Second, in economies at an intermediate level of financial development, full financial liberalization my actually destabilize the economy. On the other hand, foreign direct investment does not destabilize.
Keywords: 330; Finanzmarktregulierung; Wirtschaftskrise; Volatilität; Schock; Auslandsinvestition; Theorie